The The Influence of Human Resource Capabilities, Accounting Information Systems, and Financial Supervision on the Financial Reports Quality in Ngemplak Sub-District: Pengaruh Kemampuan Sumber Daya Manusia, Sistem Informasi Akuntanai, dan Pengawasan Keuangan Terhadap Kualitas Laporan Keuangan di Kecamatan Ngemplak - Septi Wulandari; Rismawati Wahyu Ningtyas; Dika Rahayuningsih; Amy Wulandari; Nur Asih Triatmaja (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of the observation is to see the partial impact between the ability of Human Resources, Accounting Information Systems, and auditing on the quality of financial statements. Village officials in the Ngemplak sub-district are the object of this research. Data collection techniques using questionnaires as many as 36 samples with purposive sampling techniques, while data analysis with multiple linear regression analysis. Data instrument testing techniques use validity tests, reliability tests, and classic assumption tests. Based on the partial test results, it is known that HR capabilities have a negative and insignificant impact on the quality of financial reports by 0.176 > 0.05, Accounting Information Systems have a positive and significant effect on the quality of financial reports by 0.000 > 0.05, and auditing has a positive and significant effect on the quality of financial reports by 0.000 > 0.05, and the R2 test results are 0.822 or 82.2%.